Losing the Eyes in the Back of Our Heads : Social Service Skills, Lean Caring, and Violence - Baines, Donna (2004)
Violence in the social services work place in general, and the developmental services in particular,h as increased in the last several years. Findingsf rom an ethnographic study suggests that new, lean forms of work organization remove opportunities to use or learn many of the tacit or practice skills workers previously used to keep themselves and their clients safer in the work place. This article describes many of these skills and the new management schemes that remove the possibility to develop or transmit these praxis skills. The article concludes by analyzing the convergence between the new labour processes and the competency approach to work place skills. Noting the loss of praxis skills that kept workers and clients safer, the conclusion highlights the hidden costs to developmental sector clients and workers